Emprego em TICs e gênero no ramo de informática: uma primeira exploração - Zuleica Lopes Cavalcanti de Oliveira; João Raposo Belchior (Ciências Sociais Unisinos)
This work aims to raise some points that allow a better understanding about the dynamics of female participation in computer sector in the Brazilian society in recent period. The question that guides this study is related to the following points: (a) the extent to which gender differences in the labor market have played in the computer sector (b) to what extent women's participation in this sector has experienced changes worth noting. Moreover, this work is based on government statistics, since there are still few quantitative nature of the analysis on the trends of female employment in the computer sector.